1971
DOI: 10.1017/s0003356100029494
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns of muscles of Merino sheep from birth to 517 days

Abstract: SUMMARYEighty-two Merino sheep from birth to 517 days old were dissected into individual muscles. A system of overlapping growth coefficients was used to classify the growth patterns of 96 muscles and nine muscle groups. The relative size of muscles and groups at birth and one year are expressed as percentages of total half-carcass muscle weight.Some differences were noted from the previously recorded growth patterns of bovine muscles. The groups of muscles in the proximal part of the pelvic limb and those sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
30
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 5 publications
5
30
0
1
Order By: Relevance
“…Meat proportions of the breast rib and neck did not change significantly ( Table 4), while that of the flank was a mirror image of changes in SCF (Table 2), by declining between fat scores 1 to 3 with no significant variation between fat scores 3 and 5. As a result of the high increase in SCF proportions over all fat scores, % meat in the loin declined significantly (P <0.05) between fat score 1 and 5 While some work has been reported on the proportional development of muscles in cattle (Berg & Butterfield (1978) and sheep (Lohse et al, 1971;Palsson & Verges, 1952;Thonney et al, 1987), it is difficult to relate these results with the yield of commercial cuts, since anatomical muscle grouping often extends over cuts or various groups are contained within a commercial cut. Moreover, meat and not muscle yield was reported in the present study and therefore IMF was included in the proportions reported.…”
Section: Resultsmentioning
confidence: 94%
“…Meat proportions of the breast rib and neck did not change significantly ( Table 4), while that of the flank was a mirror image of changes in SCF (Table 2), by declining between fat scores 1 to 3 with no significant variation between fat scores 3 and 5. As a result of the high increase in SCF proportions over all fat scores, % meat in the loin declined significantly (P <0.05) between fat score 1 and 5 While some work has been reported on the proportional development of muscles in cattle (Berg & Butterfield (1978) and sheep (Lohse et al, 1971;Palsson & Verges, 1952;Thonney et al, 1987), it is difficult to relate these results with the yield of commercial cuts, since anatomical muscle grouping often extends over cuts or various groups are contained within a commercial cut. Moreover, meat and not muscle yield was reported in the present study and therefore IMF was included in the proportions reported.…”
Section: Resultsmentioning
confidence: 94%
“…Para os cordeiros ocorreu o inverso: a paleta apresentou maiores porcentuais de gordura intermuscular (Tabela 3) do que o lombo e a perna, que não diferiram entre si (p>0,05), com valor médio de 2,51%. Isto se deve à precocidade de desenvolvimento dos tecidos da paleta, em relação aos demais cortes da carcaça (Lohose et al, 1971;Osório et al, 1995).…”
Section: Resultsunclassified
“…Muscularity values were calculated for the anatomical areas involving muscles (listed in brackets after the relevant bone) around or beside several bones including the femur (M. semimembranosus, M. semitendinosus, M. biceps femoris, M. quadriceps femoris, M. adductor), tibia (muscles of the distal part of the pelvic limb (Lohse et al 1971)), all leg bones combined (measured on the intact leg as the distance from the distal end of the Table 1 Numbers of animals within the age groups together with the year of birth and the approximate age at slaughter for each age group, and within each line (1 = High-backfat line; 2 = Low-backfat line). (Lohse et al 1971)).…”
mentioning
confidence: 99%
“…(Lohse et al 1971)). Corresponding values for muscle to bone ratios (M:B) for the same six bones or sets of bones and muscles were also calculated.…”
mentioning
confidence: 99%